Don't shoot!: State-wide police shootings, adolescent risk-taking behaviors, and the historic influence of wealth - Smith, Nina; Harper, Jim; Smith, Ché; Young, Deja (Advances in Social Sciences Research Journal, 2020)
The present study uses Bronfenbrenner’s ecological systems theory as a framework for understanding the influence of state-wide fatal police shootings and wealth on a host of adolescent risk-taking behaviors (i.e. sexual risk taking, tobacco use, drug use, alcohol use, and suicide risk). Using data from the Youth Risk Behavior Survey, associations were tested among black and white adolescents from five states (N=13,314). State-wide police shootings were positively associated with drug use, alcohol use, and suicide risk among black adolescents. In contrast, state-wide police shootings, alone, were not associated with any risk-taking behaviors among white adolescents. However, wealth mattered, such that increases in wealth were significantly associated with lower sexual risk-taking, drug use, and suicide risk for white adolescents. Wealth was only associated with lower alcohol use among black adolescents. Our results indicate that state-wide fatal police shootings may shape adolescent health in unfavorable ways – namely among Black youth. Wealth may serve as a buffer against the negative effects of state-wide fatal police shootings.